2018
DOI: 10.1038/s41386-018-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent regulation of social reward by oxytocin: an inverted U hypothesis

Abstract: The rewarding properties of social interactions are essential for the expression of social behavior and the development of adaptive social relationships. Here, we review sex differences in social reward, and more specifically, how oxytocin (OT) acts in the mesolimbic dopamine system (MDS) to mediate the rewarding properties of social interactions in a sex-dependent manner. Evidence from rodents and humans suggests that same-sex social interactions may be more rewarding in females than in males. We propose that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 174 publications
(219 reference statements)
3
48
0
Order By: Relevance
“…These studies were conducted in Syrian hamsters, a species particularly well-suited for the preclinical study of behaviors that underlie psychiatric health and illness [18], and are consistent with recent evidence in humans that women find positive social interactions with same-sex partners to be more rewarding than men do [19]. Further, we test the overarching hypothesis that there is an inverted U-shaped relationship between duration of social interaction and social reward that is mediated by OT in both males and females, and that this dose-response relationship is initiated at lower doses in females than males [8]. Understanding the sex differences in the mechanisms of social reward is particularly important because deficits in social reward are linked with a variety of psychiatric disorders [20,21], many of which are sex-dependent in terms of prevalence and predispositions, e.g., autism spectrum disorder [22].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…These studies were conducted in Syrian hamsters, a species particularly well-suited for the preclinical study of behaviors that underlie psychiatric health and illness [18], and are consistent with recent evidence in humans that women find positive social interactions with same-sex partners to be more rewarding than men do [19]. Further, we test the overarching hypothesis that there is an inverted U-shaped relationship between duration of social interaction and social reward that is mediated by OT in both males and females, and that this dose-response relationship is initiated at lower doses in females than males [8]. Understanding the sex differences in the mechanisms of social reward is particularly important because deficits in social reward are linked with a variety of psychiatric disorders [20,21], many of which are sex-dependent in terms of prevalence and predispositions, e.g., autism spectrum disorder [22].…”
Section: Introductionsupporting
confidence: 78%
“…We have presented an inverted U-shaped hypothesis as a heuristic tool with which to consider how valence, both positive and negative, is assigned to social stimuli in a sex-dependent manner [8]. This hypothesis proposes that as the dose (i.e., duration or intensity) of social interactions increases, their rewarding nature is initially increased, but ultimately reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to an increasing number of task-based OXT administration studies, no sex-differential effects of OXT were observed during the task-free state. Previous studies reported differential effects of OXT on men and women during social evaluation and social interaction (Borland et al, 2018;Feng et al, 2015;Gao et al, 2016) even when stimuli are presented subliminally . The lack of sexdifferential effects during the task-free state suggests that sex-differential effects of OXT evolve in interaction with the social context.…”
Section: Sex-dependent Effects Of Oxtmentioning
confidence: 97%
“…An additional behavioral measure that has become a key feature in preclinical models for neurodevelopmental disorders, especially for autism studies, is social behavior. Borland et al review the current state of sex differences in the presentation and development of social behaviors in humans and animal models, and discuss the potential therapeutic efficacy of oxytocin in social reward and treatment of social dysfunction [23].…”
mentioning
confidence: 99%